2018
DOI: 10.1136/bmjopen-2017-019388
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sex work on risk behaviours and their association with HIV positivity among people who inject drugs in Eastern Central Canada: cross-sectional results from an open cohort study

Abstract: ObjectivesThe objectives of this study were: (1) to examine the correlates of HIV positivity among participants who injected drugs and engaged in sex work (PWID-SWs) in the SurvUDI network between 2004 and 2016, after stratification by sex, and (2) to compare these correlates with those of sexually active participants who did not engage in sex work (PWID non-SWs).Design and settingThis biobehavioural survey is an open cohort of services where participants who had injected in the past 6 months were recruited ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Additionally, although there was no statistical association between biological sex and HIV infection, female PWID in our study reported a higher prevalence of selling sex for drugs consistent with other studies among female PWID [ 33 , 34 ]. PWID who also report sex work are at a higher risk of HIV acquisition compared to other PWID [ 7 ]. Furthermore, one in three female PWID was injected by a sexual partner the first time they injected a drug, which demonstrates the complex interplay of sexual and IDU practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, although there was no statistical association between biological sex and HIV infection, female PWID in our study reported a higher prevalence of selling sex for drugs consistent with other studies among female PWID [ 33 , 34 ]. PWID who also report sex work are at a higher risk of HIV acquisition compared to other PWID [ 7 ]. Furthermore, one in three female PWID was injected by a sexual partner the first time they injected a drug, which demonstrates the complex interplay of sexual and IDU practices.…”
Section: Discussionmentioning
confidence: 99%
“…PWID additionally face significant social and economic challenges, as often demonstrated by their high burdens of homelessness, unstable housing, and incarceration rates [ 1 ]. Finally, PWID have overlapping sexual risks with high levels of inconsistent condom use and sex work [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the fact that some PWID in the sample self-identify as MSM suggest existence of groups of PWID who may have substantial sexual risk of HIV and other STI compared to other PWID in Rwanda. For instance, PWID who also engage in sex work have been found to be at higher risk of HIV compared to other PWID 8 . Thus, programs should be cognizant of this complex interplay of sexual identities; and sexual and IDU practices to offer optimal interventions to all members of KP groups.…”
Section: Discussionmentioning
confidence: 99%
“…PWID additionally face significant social and economic challenges with high burden of homelessness or unstable housing and high incarceration rates 2 . Finally, PWID have overlapping sexual risks with high levels of inconsistent condom use and sex work 8 .…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of personal information files (PIF) are stored on the servers of universities, hospitals and public health research centres. This information is collected for public health activities, such as the surveillance of cancers or infectious diseases [17] or for research purposes [18], sometimes with and at other times without individual consent [8,10,12,19]. In Québec, public health stakeholders or researchers may have access to personal information without individual consent, with permission granted by institutional actors such as the Director of Professional Services of a hospital [20,Art.…”
Section: An Inequitable Transparency Requirementmentioning
confidence: 99%